A microwave-powered continuous fluidic system for polymer nanocomposite manufacturing: A proof-of-concept study - Torabfam, Milad; Nejatpour, Mona; Fidan, Tuçe; Kurt, Hasan; Yüce, Meral; Bayazıt, Mustafa Kemal (Royal Society of Chemistry, 2022)
Continuous manufacturing of pure nanocrystals with a narrow size distribution in a polymer matrix is very challenging, although it is highly crucial to get their full potential for advanced applications. A long-lasting nanocomposite (NC) manufacturing challenge is, for the first time, overcome by a microwave-powered fluidic system (MWFS). The effect of microwave power (MWP), flow rate, and the concentration of the reagents are systematically studied. The nylon-6 NC bearing evenly distributed silver nanoparticles (AgNPs) with a mean size of similar to 2.59 +/- 0.639 nm is manufactured continuously in similar to 2 min at similar to 50-55 degrees C using a green solvent, formic acid. The AgNP size becomes smaller when increasing the polymer concentration gradually. Small NPs with a narrow size distribution are produced at high MWP (40 W), but large ones with a broad size distribution at low MWP (10 W). The nylon-6 crystallinity is NP size-dependent, and the gamma-phase (pseudo-hexagonal crystal) is dominant in the presence of small NPs as against the large counterparts. Given the small-sized AgNPs in the MWF-manufactured NCs, the antibacterial activity tests with Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa show superior activity compared to that of the large AgNP-bearing (similar to 50 nm) NCs produced in a conventional heating fluidic system. The proposed MWFS can manufacture other added-value NCs continuously.
Keywords: Polymer Nanocomposite Manufacturing; Fluidic System; Microwave